2020
DOI: 10.1080/15384047.2020.1736483
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of NSAIDs administration as double-edged agents against endometrial cancer and pathological species of the uterine microbiome

Abstract: Many types of cancers, including endometrial cancer, were found to have cyclooxygenase-2 (COX-2) overexpression. Because this enzyme belongs to the group of pro-inflammatory enzymes, so-called NSAIDs (non-steroidal anti–inflammatory drugs) directly inhibit its activity. An increasing number of reports on COX-2 involvement in cancer, as well as on the role of microbiota in abnormal metabolism and signaling of cells, forces the development of new NSAID types. Besides, NSAIDs can affect some bacteria, which are v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 98 publications
(112 reference statements)
1
15
0
3
Order By: Relevance
“…Interestingly, some NSAIDs, such as diclofenac, ibuprofen, and particularly aspirin, have antimicrobial properties by inhibiting processes such as bacterial growth, adhesion, and biofilm formation. Considering the potential role of the cancer-associated endometrial microbiota in the induction of inflammation by stimulating the production of COX-2 in carcinogenesis, NSAIDs will have additive effects in inhibiting the disease progress through inhibiting bacterial growth and inflammation (Kuzmycz & Staczek 2020). However, it is necessary to perform more studies to ascertain the carcinogenic processes induced by bacteria, the influence of NSAIDs in microbial viability, and their potential secondary effects.…”
Section: Endometrial Cancermentioning
confidence: 99%
“…Interestingly, some NSAIDs, such as diclofenac, ibuprofen, and particularly aspirin, have antimicrobial properties by inhibiting processes such as bacterial growth, adhesion, and biofilm formation. Considering the potential role of the cancer-associated endometrial microbiota in the induction of inflammation by stimulating the production of COX-2 in carcinogenesis, NSAIDs will have additive effects in inhibiting the disease progress through inhibiting bacterial growth and inflammation (Kuzmycz & Staczek 2020). However, it is necessary to perform more studies to ascertain the carcinogenic processes induced by bacteria, the influence of NSAIDs in microbial viability, and their potential secondary effects.…”
Section: Endometrial Cancermentioning
confidence: 99%
“…Importantly, the incidence of EC is drastically rising in high-income countries ( Jonusiene and Sasnauskiene, 2021 ). Although several mechanistic events accompanying host genetic alterations and hereditary factors have been shown to play important roles in endometrial carcinogenesis, they can only explain 10–20% of cases ( Walther-António et al., 2016 ; Kuźmycz and Stączek, 2020 ). Efforts to identify the cause of the remaining 80–90% of cases have led to studies on a number of environmental factors, including hormones, obesity, inflammation, and menopausal status, which are major risk factors for the development of type I EC ( Beral et al., 2005 ; Morice et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…to play important roles in endometrial carcinogenesis, they can only explain 10-20% of cases (Walther-Antońio et al, 2016;Kuzḿycz and Staczek, 2020). Efforts to identify the cause of the remaining 80-90% of cases have led to studies on a number of environmental factors, including hormones, obesity, inflammation, and menopausal status, which are major risk factors for the development of type I EC (Beral et al, 2005;Morice et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we showed that treatment with the non-steroidal anti-inflammatory drug (NSAID) meloxicam from 10 to 13 DIM transiently reduced haptoglobin (a marker of systemic inflammation) and improved indicators of energy metabolism (greater insulin-like growth factor-1 and glucose, and lesser β-hydroxybutyrate), and modestly increased circulating polymorphonuclear (PMN) cell function [ 14 ]. Furthermore, antibacterial properties of some NSAID were recently discovered [ 15 ]. Diclofenac, aspirin, and etodolac could prevent biofilm formation at normal doses used during anti-inflammatory therapy [ 16 ].…”
Section: Introductionmentioning
confidence: 99%